Intrinsic Capacity vs. Multimorbidity: A Function-Centered Construct Predicts Disability Better Than a Disease-Based Approach in a Community-Dwelling Older Population Cohort - Zhao, Jing; Chhetri, Jagadish K.; Chang, Yi; Zheng, Zheng; Ma, Lina; Chan, Piu (Frontiers in Medicine, 2021)
Objective: This study aimed to assess the status of Intrinsic capacity (IC) - a novel function-centered construct proposed by the WHO and examine whether impairment in IC predicts subsequent one-year activities of daily living (ADL) disability better than a disease-based approach i.e., multimorbidity status. Methods: This study included data of community-dwelling older adults from the Beijing Longitudinal Study on Aging II aged 65 years or older who were followed up at one year. Multivariate logistic regressions were performed to estimate the odds of ADL disability at baseline and one-year follow-up. Results: A total of 7298 older participants aged 65 years or older were included in the current study. 4742 older adults were followed up at one year. At baseline, subjects with a higher impairment in IC domains showed higher odds of ADL disability (adj. OR=9·51 for impairment in ≥3 domains, AUC=0.751) compared to much lower odds of ADL disability in subjects with a higher number (≥3) of chronic diseases (adj. OR 3·92, AUC=0.712). At one year follow-up, the overall incidence of ADL disability increased with the impairment in IC domains higher than the increase in multimorbidity status. A higher impairment in IC domains showed higher odds of incidence ADL disability for impairment in 2 or ≥3 IC domains (adj. OR 2·32 for impairment in ≥3 domains, adj. OR 1·43 for impairment in 2 domains, AUC=0.685). Only subjects who had ≥3 chronic diseases had higher odds of one-year incident ADL disability (adj. OR 1·73, AUC=0.681) that was statistically significant. Conclusion: Our results imply that a function-centered construct could have higher predictability of disability compared to the multimorbidity status in community older people. Our results need to be confirmed by studies with longer follow-up. Keywords: ICOPE; Integrated care; Comorbidity; Aging; Ageing; Older Chinese;